Trends in Prevalence of Overweight and Obesity in Korean Adults, 1998–2009: The Korean National Health and Nutrition Examination Survey - Kang, Hee-Taik (Japan Epidemiological Association, 2014)
BACKGROUND: Although obesity is increasing worldwide and becoming a major public health problem, some countries report a trend toward stabilization. We investigated prevalence trends in overweight/obesity and obesity among Korean adults during a 12-year period. METHODS: This study was based on the Korean National Health and Nutrition Examination Survey (KNHANES) I (1998), II (2001), III (2005), and IV (2007–2009). The χ(2) and ANOVA tests were used to compare the prevalence and mean values for age and BMI, respectively. P-values for trends were determined by linear and logistic regression analyses, with KNHANES phase as the continuous variable. RESULTS: The prevalences of overweight/obesity in KNHANES I through IV were 50.8%, 57.4%, 62.5%, and 62.6%, respectively, among men (P for trend = 0.002, β = 0.021) and 47.3%, 51.9%, 50.0%, and 48.9% among women (P for trend = 0.017, β = −0.015). The respective prevalences of obesity were 26.0%, 32.4%, 35.1%, and 36.3% among men (P for trend = 0.006, β = 0.018) and 26.5%, 29.3%, 28.0%, and 27.6% among women (P for trend = 0.143, β = −0.008). During the same period, the respective prevalences of grade 2 obesity (BMI ≥30 kg/m(2)) were 1.7%, 2.8%, 3.6%, and 3.8% among men (P for trend = 0.075, β = 0.005) and 3.0%, 3.5%, 3.4%, and 4.0% among women (P for trend = 0.398, β = 0.003). CONCLUSIONS: The prevalences of overweight/obesity and obesity showed an upward trend among men during the 12-year period, whereas the prevalence of overweight/obesity slightly decreased among women from 2001.